2009
DOI: 10.1119/1.3139533
|View full text |Cite
|
Sign up to set email alerts
|

What course elements correlate with improvement on tests in introductory Newtonian mechanics?

Abstract: In an MIT calculus-based introductory Newtonian mechanics course, we study the effectiveness of various instructional course elements: electronic and written homeworks, collaborative group problems, and class participation. We measure effectiveness by the slope of the regression line between a student’s score (used as a proxy for participation) on a particular course element and his normalized gain on various assessment instruments. These instruments were the MIT final exam comprised mainly of multipart proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Time represents the principal cost function for students, so it is important to study how students allocate time among available course components. 15,19 Figure 4 shows the most time is spent on lecture videos; since three to four hours per week is close to the total duration of the scheduled videos, students who rewound and reviewed the videos must compensate for those speeding up playback or omitting videos.…”
Section: Resultsmentioning
confidence: 99%
“…Time represents the principal cost function for students, so it is important to study how students allocate time among available course components. 15,19 Figure 4 shows the most time is spent on lecture videos; since three to four hours per week is close to the total duration of the scheduled videos, students who rewound and reviewed the videos must compensate for those speeding up playback or omitting videos.…”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing paper-and-pencil homework to Web-based homework have found mixed results, with some studies citing no differences in performance [194] and others citing improved performance with Web-based tutors or homework systems [195][196][197][198]. Additional research results about homework are summarized in Sec.…”
Section: Instructional Strategiesmentioning
confidence: 99%
“…As stated in the section on Problem Solving, there are several Web-based homework systems in physics including the "computer-assisted personalized assignment" system CAPA [120,[191][192][193], Mastering Physics, WebAssign [560], and CyberTutor [121]. Studies comparing paperand-pencil homework to Web-based homework have found mixed results, with some studies citing no differences in performance [194] and others citing improved performance with Web-based tutors or homework systems [195][196][197][198].…”
Section: Course Exams and Homeworkmentioning
confidence: 99%
“…Computer usage (as opposed to computation) is ubiquitous in large introductory courses, and much work has been done to understand the role of computers in these courses [4]. In contrast, little is known about the role that computers might play as problem-solving tools in introductory courses.…”
Section: Introductionmentioning
confidence: 99%